Cost effectiveness analysis of erythropoietin therapy in the ministry of health dialysis programme - Md. Yusof, Faridah Aryani (2006)
End-stage renal failure patients are normally anaemic due to failure of renal to produce endogenous erythropoietin (EPO). Erythropoietin is used to treat anaemia in these patients but the drug is expensive. The drug is also used in cancer and thalassemia patients and it makes EPO in high demand and thus increasing the budget for the government. The objectives of this study were to determine the life expectancy, the improvement in haemoglobin levels of anaemic patients associated with EPO therapy, the improvement in quality of life associated with haemoglobin, the utility oi the dialysis patients, the additional costs associated with EPO therapy and the cost effectiveness of MOH dialysis program, measured as cost per quality-adjusted life year saved. The instruments used for health-related quality of life questionnaires were EQ- 50 and Spitzer's quality of life index, and also the time trade-off method. The costs were valued in terms of year 2004 RM. The National Renal Registry (NRR) database for period 1997- 2004 formed the basis of patient selection, where data was not available the NRR database was used as the sampling frame to obtain the list of patients for the survey. Erythropoietin therapy improved the mean haemoglobin level of anaemic haemodialysis patients by 9.39% (8.97 g/dl to 9.81 g/dl) and CAPO patients 8.48% (8.96 g/dl to 9.72 g/dl) at the range of 8 to 1 0 g/dl. Mean dose of EPO prescribed at baseline haemoglobin level between 8 to 10 g/dl was 4679 U per week for haemodialysis patients and 44 77 U per week for CAPO patients. The mean cost to raise 1 g/dl haemoglobin per patient per year was RM527 4 for haemodialysis patients and RM4887 for CAPO patients at same haemoglobin levels. Overall life expectancy on dialysis was 10.13 years with superior life expectancy for haemodialysis (11.37 years) compared to CAPO. (7.94 years). Age at commencement of dialysis, diabetic status, haemoglobin level, albumin level and dialysis modality were significant predictors of life expectancy. Quality of life of CAPO patients was higher among the dialysis patients (0.79 to 0.93) of perfect health equivalent compared to haemodialysis patients (0.79 to 0.89) of perfect health equivalent. The cost of dialysis was RM33,958 for haemodialysis and RM33,243 for CAPO per patient per year. The cost per quality-adjusted life years was RM43,000 for haemodialysis and • RM41 ,000 for CAPO. The incremental QAL Ys gained for haemodialysis and CAPO patients at ha~moglobin baseline were 2.04 and 0.27, respectively. The incremental cost per QALY gained of EPO was RM66,000 and RM137,000 for haemodialysis and CAPO patients, respectively at the same average baseline haemoglobin level between 8 g/dl and 10 g/dl. In conclusion, haemodialysis is more cost effective modality with the current state of utilisation of EPO therapy. Keywords: Haemodialysis, Continuous Ambulatory Peritoneal Dialysis, Erythropoietin, Anaemia, Cost-effectiveness, Quality of Life, TTO, Qualityadjusted Life Years, Ministry of Health